Jenis dan Nilai Ekonomi Hasil Hutan Bukan Kayu Terhadap Suku Anak Dalam Di Taman Nasional Bukit Duabelas - Maria Ulfa; Albayudi Albayudi; Mitaria Sirait (Jurnal Silva Tropika, 2019)
Suku Anak Dalam (SAD) is a traditional tribe in Jambi Province. They live in the forest and utilize forest products including non-timber forest products (NTFPs) to meet their daily needs. One of the SAD population areas is in the Bukit Duabelas National Park (TNBD). The purpose of this study was to determine the type and economic value of NTFPs that SAD utilized to meet its economic needs in TNBD. The study was conducted in January-May 2019 in the buffer village of TNBD with the method of field observation, interviews and literature review. Respondents were determined by simple random technique while the number of respondents was determined by Slovin Technique. Data were analyzed descriptively after complete tabulation. The results showed that there were 10 types of NTFPs that were utilized economically by SAD. The highest economic value of NTFPs is Rattan with a total value of Rp. 554,887, 000 / year or with a proportion reaching 53.25% while the lowest economic value of NTFPs is Balam sap with an economic value of Rp. 1,800,000 / year with a proportion of 0.17%. From these results it can be concluded that NTFPs have enormous benefits to the SAD economy and livelihood in TNBD.